Coastal land use planning in Ben Tre, Vietnam: constraints and recommendations. Issue 4 (April 2019) - Nguyen, Tan Phong; Parnell, Kevin E.
Abstract: There have been few reviews of the effectiveness of the management of coastal mangrove protected areas and coastal land use planning at all levels in the Mekong Delta, Vietnam. Ben Tre province provides a good case study to enable the assessment of typical management practices in the provinces of the Delta. The study aims to critically review the current strategies for managing the Ben Tre coast and to consider what changes are required to ensure effective coastal management. The current coastal management strategies only dealt with symptoms and worked temporarily. There has been insufficient coordination in land use planning and coastal management among the Ben Tre government agencies, substantially contributing to mangrove loss and degradation. Natural regeneration of local mangrove species and secondary succession, although having been practically effective for protecting from coastal erosion, have not been used as coastal management measures. Three strategies, hold the existing defence line, managed realignment, and no active intervention, are recommended to assist in managing the Ben Tre coast for adaptation to climate change and sea level rise, and livelihood improvement.